Nucleotide variation in Sabin type 3 poliovirus from an Albanian infant with agammaglobulinemia and vaccine associated poliomyelitis. Issue 1 (December 2016) - Foiadelli, Thomas; Savasta, Salvatore; Battistone, Andrea; Kota, Majlinda; Passera, Carolina; Fiore, Stefano; Bino, Silvia; Amato, Concetta; Lozza, Alessandro; Marseglia, Gian; Fiore, Lucia
Abstract Background Vaccine-associated paralytic poliomyelitis (VAPP) and immunodeficient long-term polio excretors constitute a significant public health burden and are a major concern for the WHO global polio eradication endgame. Case presentation Poliovirus type 3 characterized as Sabin-like was isolated from a 5-month-old Albanian child with X-linked agammaglobulinemia and VAPP after oral polio vaccine administration. Diagnostic workup and treatment were performed in Italy. Poliovirus replicated in the gut for 7 months. The 5' non coding region (NCR), VP1, VP3 capsid proteins and the 3D polymerase genomic regions of sequential isolates were sequenced. Increasing accumulation of nucleotide mutations in the VP1 region was detected over time, reaching 1.0 % of genome variation with respect to the Sabin reference strain, which is the threshold that defines a vaccine-derived poliovirus (VDPV). We identified mutations in the 5'NCR and VP3 regions that are associated with reversion to neurovirulence. Despite this, all isolates were characterized as Sabin-like. Several amino acid mutations were identified in the VP1 region, probably involved in growth adaptation and viral persistence in the human gut. Intertypic recombination with Sabin type 2 polio in the 3D polymerase region, possibly associated with increased virus transmissibility, was found in all isolates. Gamma-globulin replacement therapy led to viral clearance and neurological improvement, preventing the occurrence of persistent immunodeficiency-related VDPV. Conclusions This is the first case of VAPP in an immunodeficient child detected in Albania through the Acute Flaccid Paralysis surveillance system and the first investigated case of vaccine associated poliomyelitis in Italy since the introduction of an all-Salk schedule in 2002. We discuss over the biological and clinical implications in the context of the Global Polio Eradication Program and emphasize on the importance of the Acute Flaccid Paralysis surveillance.